Ó Senhor, Deus das vinganças, resplandece (Sl 94.1): A legitimidade e a interpretação dos Salmos de vingança - Marcel Wanke, Roger (Vox Scripturae - Revista Teológica Internacional, 2013)
Vengeance psalms are integral part of the Bible and, at the same time, the most integral prayers of the Bible. Recently, many have asked themselves of the legitimacy and the  interpretation of such psalms, especially in the Christian context, marked by Jesus’ words, which requires to love the enemies and to pray for these. The article seeks to understand the vengeance psalms, first of all, in its biblical and historical context. At a second moment, the concentration will be on the comprehension of these psalms in the works of Martin Luther and Dietrich Bonhoeffer, which, in the context of theology’s history, occupied themselves not only with the psalms in general, but also, specifically, with the vengeance psalms. At a third moment, the article will concentrate in the recent discussion on the interpretation of the vengeance psalms in the context of the Old Testament exegesis, which presents them, as called by it, as post-cultic phenomenon (“nachkultisches Phänomen”). At last, three tasks will be presented for the theological research and for the Church, which has as incumbency the discussion on the relevancy and the legitimacy of the vengeance psalms in the context of the Christian spirituality. The Book of Psalms exists to give the correct words to the one who prays, when this one does not have them, as much in the sublime experience of worship and gratitude to God, as when experiencing sorrow and suffering in life. It is also this way in relation to the vengeance psalms
Keywords: Old Testament; Hermeneutics; Book of Psalms; Vengeance